Perspektif Karyawan Tentang Kepemimpinan Terhadap Kepuasan Kerja - Faisal Arief Akhmad Prasojo; Muhammad Furqon; Bagus Dwi Priyanto; Sentot Imam Wahjono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore employee perspectives on leadership and its impact on job satisfaction.Leadership is a crucial factor that shapes employees' perceptions and attitudes toward their work. Thisstudy uses a qualitative approach with in-depth interview techniques to explore employees' views on theleadership style implemented and its impact on job satisfaction. Data analysis was conducted thematicallyto identify patterns in employee perceptions. The results reveal that employees perceive communicative,fair, and supportive leadership as significantly enhancing their job satisfaction. Employees also emphasizethe importance of leaders who are able to listen to aspirations and provide clear direction. These findingsprovide valuable insights for management to develop leadership practices that are more responsive toemployee needs in order to improve job satisfaction and work productivity.